Original Research Article Analysis of Factors Influencing the Incidence of Dysmenorrhea - Mukhoirotin; Rohman, Zanna Alfiyatur (Jurnal Kebidanan Midwiferia, 2024)
Globally, the prevalence of dysmenorrhea in women is still high. Dysmenorrhea in adolescent girls that is not treated can interfere with daily activities and learning activities. Therefore, adolescents need to learn and understand the factors that affect dysmenorrhea. This study aims to determine the factors that influence the incidence of dysmenorrhea. This study was case control in design. The study included 300 participants, 120 of whom were selected using the purposive sampling technique from among the adolescent girls in the Muzamzamah Chosyi'ah Dormitory of Darul 'Ulum Islamic Boarding School. A questionnaire was employed as the research tool. At a significance level of α <0.05, the data were analyzed using the chi-square test and logistic regression. The results of the analysis test showed that there was no effect of menarche age and the number of menstrual flow on the incidence of dysmenorrhea (p>0.05). The incidence of dysmenorrhea was influenced (p<0.05) by the menstrual cycle, duration of menstruation, family history, and BMI. The dominant factor influencing the incidence of dysmenorrhea was family history (p=0.000; Exp(B): 129.98). Family history of dysmenorrhea has a greater potential for the occurrence of dysmenorrhea because it is related to genetic factors that pass on traits to their offspring. It is recommended to adopt a healthy lifestyle such as exercising regularly, fulfilling balanced nutritional needs, and maintaining ideal body weight.